The role of cash incentives in HIV behaviour change: A case study based on the RHIVA programme in Namibia (Journal for Studies in Humanities and Social Sciences, 2020)
This study explores the use of cash incentives towards positive behaviour change amongstadolescents at different schools in the Khomas Region, Windhoek, Namibia. The aim of theresearch was to assess the efficacy of the Reducing HIV/AIDS in Adolescents (RHIVA)programme’s cash incentive-based theory of change. The hypothesis of the model is that cashincentives can promote positive behavioural change. The behaviour change is related to HIV/AIDSprevention and other behavioural patterns more specific to adolescents. The study used secondarydata from a pre-post quasi-experimental research design collected between 2013 and 2015. Theprimary data came from 529 responses to a baseline survey and 458 responses to an end-line surveyconducted in the Khomas Region. The secondary analysis explored the impact of cash incentiveson learners’ sexual behaviour, especially the learners who received full RHIVA intervention (IG2).The study concludes that the full RHIVA programme intervention resulted in a 10% reduction in sexual activity. The RHIVA programme is effective for learners younger than 16 years and for females from middle to high-income areas. However, the study found that cash incentives do not result in an increase in the number of times that learners were tested for HIV. It also found that direct cash payments to learners have the potential to be both a deterrent and an incentive for positive behaviour change as direct cash payments are prone to other socio-structural pressures such as the prevalence of alcohol and drug use at school and community levels. The study further concludes that conditional cash transfers remain very important in increasing the HIV Counsellingand Testing (HCT) uptake of learners despite certain limitations.
Keywords: HIV/AIDS prevention; behaviour change; cash incentives; adolescents; HIV Counselling and Testing (HCT) uptake